Efektivitas Kegiatan Syahrul Lughoh terhadap Peningkatkan Keterampilan Berbicara Bahasa Arab Mahasiswi STIT Madani Yogyakarta Tahun 2024 - Imroatul Toyibah Nurrohim; Amrin Mustofa (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study examines the effectiveness of the Syahrul Lughoh program in improving Arabic speaking skills among female students at STIT Madani Yogyakarta in 2024. The research uses a quantitative approach with a non-experimental survey design, involving 36 respondents selected through purposive sampling from the second, fourth, sixth, and eighth-semester students. The data analysis shows a mean score of 3.384 and a mode of 4, indicating the program’s high effectiveness in enhancing Arabic speaking skills. Among the various activities, the Ilqoul Mufrodat program proved to be the most effective, with a mean score of 3.569, followed by Daurah Masyaikh (3.379), Kitab Al-‘Arabiyyah Baina Yadaik (3.351), and Arabic Fun (3.235). These programs contributed significantly to improving students' abilities in vocabulary, grammar, fluency, pronunciation, and confidence in speaking Arabic. Key supporting factors for the success of the program include a pesantren-based environment that promotes daily Arabic use, a strong academic culture requiring Arabic in both academic and religious activities, and an interactive teaching method based on halaqah. However, challenges such as rushed preparation, insufficient mentor training, limited facilities, and low student motivation hindered the program’s effectiveness. The findings suggest areas for improvement in future program implementations.